2000
DOI: 10.1086/313918
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Aspergillemia in Patients with Cancer: A 10-Year Study

Abstract: The significance of blood cultures positive for Aspergillus species for patients with cancer remains unclear. The significance of aspergillemia in 36 cancer patients over a 10-year period was evaluated. True aspergillemia was rare, occurred late in the course of aspergillosis, and was seen exclusively in patients with hematologic malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
1
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 6 publications
(8 reference statements)
2
60
1
3
Order By: Relevance
“…In concert with our observation, aspergillemia in patients with cancer who did not undergo hematopoietic stem cell transplantation seldom was observed as "clinically significant" or "definite" hematogenous mycosis. 3,4 Similar to the current study ( Table 2), other studies have shown that the presence of non-Candida fungal blood isolates in most transplantation recipients with profound immunosuppression most likely represents contamination from an environmental source, suggesting "clinically nonsignificant fungemia" or "pseudofungemia." 1,2 In a retrospective analysis of Aspergillus species fungemia in patients with cancer, nearly 20% of all Aspergillus species-positive blood cultures were reported as representing "definite" mycoses; however, using the existing guidelines, 86% of those diagnoses could be established on postmortem examination only.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…In concert with our observation, aspergillemia in patients with cancer who did not undergo hematopoietic stem cell transplantation seldom was observed as "clinically significant" or "definite" hematogenous mycosis. 3,4 Similar to the current study ( Table 2), other studies have shown that the presence of non-Candida fungal blood isolates in most transplantation recipients with profound immunosuppression most likely represents contamination from an environmental source, suggesting "clinically nonsignificant fungemia" or "pseudofungemia." 1,2 In a retrospective analysis of Aspergillus species fungemia in patients with cancer, nearly 20% of all Aspergillus species-positive blood cultures were reported as representing "definite" mycoses; however, using the existing guidelines, 86% of those diagnoses could be established on postmortem examination only.…”
Section: Discussionsupporting
confidence: 79%
“…1,2 In a retrospective analysis of Aspergillus species fungemia in patients with cancer, nearly 20% of all Aspergillus species-positive blood cultures were reported as representing "definite" mycoses; however, using the existing guidelines, 86% of those diagnoses could be established on postmortem examination only. 3 This inadequacy of positive and negative predictive values of the existing diagnostic tests raises serious concerns regarding the limitations of the existing parameters for diagnosing "clinically significant" bloodstream invasion due to low-virulence, saprophytic, environmental molds. 2,4 Patients with hematologic malignancies, 3,14 recipients of hematopoietic stem cell transplantation, and patients receiving cytotoxic therapy for posttransplantation complications, such as GVHD, are at increased risk for disseminated fungal infections of non-Candida organisms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations